Social Impact of Psychological Research on Well-Being Shared in Social Media - Pulido, Cristina M.; Mara, Liviu-Catalin; Ionescu, Vladia; Sordé-Martí, Teresa (Frontiers in Psychology, 2020)
The purpose of this article is to demonstrate how the Social Impact in Social Media (SISM, hereinafter) methodology applied in psychological research contributes to making evidence of the social impact of the research visible. This article helps researchers become aware of whether and how their improvements are capturing the interest of citizens and how citizens are applying such evidence and obtaining better outcomes, in this case, in relation to well-being. In addition, citizens can access the latest evidence on social media and become channels of communication between science and social or personal networks and, in so doing, can help to improve the living conditions of others. This methodology is also useful for agencies that support researchers in psychology with financial assistance to evaluate the social impact of the funds that these agencies invest. In this article, the 10 research studies in well-being were selected for analysis under the following criteria: their research results led to demonstrable improvement in well-being, and these improvements are presented on social media. We applied the social impact coverage ratio (SICOR) to identify the percentage of the social impact shared in social media in relation to the total amount of social media data collected. Examples of quantitative and qualitative evidence of the social impact of the research on well-being are presented.